Dividing Texts. Conventions of Visual Text-Organisation in Nepalese and North Indian Manuscripts - Bhattarai, Bidur (Studies in Manuscript Cultures, 2020)
The number of manuscripts produced in the Indian sub-continent is astounding and is the result of a massive enterprise. The visual organization of texts in North Indian and Nepalese manuscripts from 800 to 1300 CE is at the centre of the present study. It sheds light on both the ways of manuscripts production and the employment of the manuscripts in ritual contexts in different areas of India and Nepal.